2021
DOI: 10.3389/fgene.2021.735348
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options in Congenital Disorders of Glycosylation

Abstract: Despite advances in the identification and diagnosis of congenital disorders of glycosylation (CDG), treatment options remain limited and are often constrained to symptomatic management of disease manifestations. However, recent years have seen significant advances in treatment and novel therapies aimed both at the causative defect and secondary disease manifestations have been transferred from bench to bedside. In this review, we aim to give a detailed overview of the available therapies and rising concepts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 140 publications
0
9
0
1
Order By: Relevance
“…Briefly, MPI-CDG can be successfully treated by oral mannose supplementation, as exogenous mannose can bypass the deficiency caused by MPI that contributes to N-glycan synthesis through Man-6-P ( Figure 2 ). International consensus guidelines recommend oral administration of mannose at a concentration of 150–170 mg/kg bodyweight, four to five times per day ( 24 ). A review of the literature revealed that of 30 patients who received mannose therapy, 26 showed improved clinical symptoms and laboratory results.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, MPI-CDG can be successfully treated by oral mannose supplementation, as exogenous mannose can bypass the deficiency caused by MPI that contributes to N-glycan synthesis through Man-6-P ( Figure 2 ). International consensus guidelines recommend oral administration of mannose at a concentration of 150–170 mg/kg bodyweight, four to five times per day ( 24 ). A review of the literature revealed that of 30 patients who received mannose therapy, 26 showed improved clinical symptoms and laboratory results.…”
Section: Discussionmentioning
confidence: 99%
“…Most of CDG families were not aware of CTs for their CDGs, clearly demonstrating different advancement levels among different CDGs. In fact, therapeutic research initiatives favour PMM2-CDG [ 10 , 21 , 22 ]. This discrepancy could be perceived as an isolating tendency towards the different CDG, thus not helping families’ involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Even though AI tools are still sporadically employed for CDG drug development, they have been successfully used for the diagnosis and characterization of these diseases [ 14 ]. Few advances in CDG therapy have been made over recent years [ 36 ]. By reviewing the literature, it is noted that four of the drugs advanced to different trial phases are repositioned drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The last few years have seen significant advancements in CDG therapy development with a few promising treatments currently under pre-clinical or clinical evaluation. The therapies include substrate or co-factor supplementation, proteostasis inhibitors, pharmacological chaperones, and antisense and gene therapy [ 36 ]. CDG drug development could be pushed by drug repositioning alone or AI-assisted approaches, as in the case of other RDs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%